2008
DOI: 10.1007/s11892-008-0084-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and approach to treatment of renal artery stenosis in patients with diabetic nephropathy

Abstract: Patients with diabetes mellitus are at increased risk for developing peripheral vascular disease and renal artery stenosis (RAS). Furthermore, in diabetic patients the progression of renal atherosclerotic disease toward critical stenosis or occlusion occurs more frequently than in their nondiabetic counterparts. Consequently, clinicians must carry a high level of suspicion for detecting RAS in diabetic patients, particularly those with established coronary and/or peripheral atherosclerotic disease and compromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…It is well known that RI, PSV, and 3 Journal of Diabetes Research eGFR were intimately linked with renal perfusion [33], and the study has shown a correlation between RI, PSV, and KBs, which also supports the above conclusions. It is well known that the patients with DM are at high risk of developing atherosclerotic renal artery stenosis (RAS) [34]. However, there is lack of consensus on the relationship between the levels of KBs and renal artery.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that RI, PSV, and 3 Journal of Diabetes Research eGFR were intimately linked with renal perfusion [33], and the study has shown a correlation between RI, PSV, and KBs, which also supports the above conclusions. It is well known that the patients with DM are at high risk of developing atherosclerotic renal artery stenosis (RAS) [34]. However, there is lack of consensus on the relationship between the levels of KBs and renal artery.…”
Section: Discussionmentioning
confidence: 99%
“…Renal artery stenosis (RAS) is a common condition in patients suffering from atherosclerosis and fibromuscular dysplasia [1][2][3][4][5][6], with an overall prevalence disease rate of 15.4% [4]. Progression to severe stenosis is well documented and leads to hypertension and kidney damage [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term hyperglycemia not only significantly impairs the microstructure of the kidney, leading to diabetic nephropathy (DN), but also causes renal artery stenosis (RAS) in diabetic patients [ 1 , 2 ]. The RAS detection rate in type 2 diabetes patients was recently reported to be 36.9% using duplex ultrasound scanning [ 3 ].…”
Section: Introductionmentioning
confidence: 99%